(untitled) (Research, Society and Development, 2019)
From the question: in what way can problem solving promote the creative potential of children in the teaching process learning the contents of addition and subtraction operations in elementary education in specialized educational service? We present in this article a result of the educational product developed in a master’s research, which brought as a proposal a didactic sequence supported by important reflections on the practice of the mathematics teacher that attends students with indicatives in high skills / giftedness. The objective is to present a didactic sequence based on the contributions of the activities of problem situations in creativity in the specialized educational service. If you want to explore the level advancement of student learning steps on orientations from a study driven using the Problem Situation Activity methodology based on Galperin’s theory so that students would develop numeracy skills in solving problems with the operations of addition and subtraction thus contributing, in their intellectual independence and creative thinking. This proposal is based on a qualitative, quantitative approach, with a qualitative focus so that the descriptive analyzes based on the data collection made with questionnaires, interviews, and observation guides, would subsidize the entire research design. Having favorable results the learning of the group of students in the different stages of assimilation through the application of the actions of the first to the second level of creativity. In this way, it is desired to emphasize to teachers who work in elementary school in the mathematics discipline, a new look to teach and motivate students in their learning.